The strain models of complex misfit dislocations at α-Fe2O3/α-Al2O3 interface. (December 2015) - Wang, Y.; Liu, X.P.; Qin, G.W.
Graphical abstract: (a and c) The experimental εxx and εyy strain distribution with overlaid circles with radii of 3 Å and 6 Å, from which line profiles are obtained. (b and d) The simulated εxx and εyy strain distributions. All the figures have the same color scale as inserted in (a). (e and f) Comparison of the circular line profiles taken from the experimental strain distribution (red lines) and simulated strain distribution (green lines) for εxx and εyy with different radii (solid lines for r  = 3 Å and dash lines for r  = 6 Å). It can be seen from the figure that the simulated results are in good agreement with the experimental results, which proves that the Foreman model with a  = 2 best describes the strain fields of the misfit dislocations. Abstract: The complex misfit dislocations with two extra half planes at α-Fe2 O3 /α-Al2 O3 interfaces were investigated by high-resolution transmission electron microscopy. Strain distributions around dislocation core were mapped using geometric phase analysis. Accurate Burgers vectors were determined by dislocation density tensor analysis to simulate strain distributions. By comparing experimental strain distributions with theoretical models, we found that all the dislocations follow the Foreman model ( a  = 2), which indicates they have the same spatial extension of strain field.